Late-stage electron-catalyzed perfluoroalkylation of coumarin derivatives—Thermal fluoroalkyl radical production from sodium perfluoroalkyl sulfinate salts - Torviso, Maria del Rosario (2017)
Novel and high-yielding protocols for the late-stage synthesis of 3-perfluoroalkyl-substituted coumarin derivatives employing either perfluoroalkyl iodides RFI or sodium perfluoroalkylsulfinate salts NaSO2RF as perfluoroalkyl RF radical precursors is presented. The electron-catalyzed methodologies make use of two comparative and parallel protocols as an entry to the production of RF radicals: (i) from NaSO2Rf sources and the thermal tert-butylhydroperoxide (TBHP) radical initiation in MeCN: CH2Cl2 as organic solvent mixture, and (ii) from commercial RFI and the photoorganocatalyst anthraquinone-2-sulfonic acid as the room-light initiation process in DMF: CH2Cl2 as mixture of solvents.